Virtual forums: dialogical forms between artists and spectators - fincortex case - Moreno Ospina, Jairo (Universidad Pedagógica y Tecnológica de Colombia, 2012)
Fincortex is a shorts fest interested in the development of these films, the encouragement of their production, and the formation of audiences. Aware of the current technological development that has originated changes in the creators and spectators’ roles –changes concerning their attitude towards art products–, in the paper it is visualized how these audiovisual arts transformations have been since the beginning of film production to present day, as well as the attitudes and commitment acquired by the artists towards sociocultural changes and by the spectators, when new attitudes for the exposed proposals are presented. Thus, it is suggested the creation of virtual forums after the projection of the shorts films so that discussion of the filmic products through horizontal dialogues is promoted, in order to consolidate a public strongly interested in these cultural products.